Anemia materna como factor predisponente de complicaciones maternas y neonatales en gestantes en el Centro de Salud San José de Ancón en el periodo noviembre 2023 – abril 2024. - Carpio Toaza, Jahaira Vanessa (2024)
Anemia is a condition that develops when the blood produces a lower than normal number of healthy red blood cells. It mainly affects women and children. Anemia occurs when the body does not have enough heme to carry oxygen to organs and tissues. In many severe cases, anemia can cause cognitive impairment and disability in children. It can also cause problems for pregnant women and their products. Anemia can be caused by poor diet, regular consumption of junk food or food of poor quality and without vitamins, infections, chronic diseases, heavy menstruation, problems during pregnancy and family history. The most common cause is a lack of iron in the blood. Anemia is the most common condition that occurs during pregnancy or is caused by a poor diet containing foods low in iron. According to prevalence studies conducted in different parts of the world, between 30 and 70 percent of pregnant women suffer from this condition, which is called anemia of pregnancy and newborn because it affects both mother and baby. Iron deficiency is the most common nutritional deficiency during pregnancy and the most common cause of anemia; depending on its intensity, it can cause difficulties in oxygen supply and affect the physiological functions of the fetus. It is associated with an increased risk of preterm delivery, low birth weight and increased perinatal mortality. Anemia affects an estimated 500 million women aged 15-49 years and 269 million children aged 6-59 months worldwide.